Hubungan Tingkat Kecemasan Terhadap COVID-19 Dengan Risiko Burnout Syndrome Pada Perawat: The Relationship between the Level of Anxiety on COVID-19 and the Risk of Burnout Syndrome in Nurses - ihsan, asep (Dohara POAJ, 2022)
Introduction: COVID-19 stands for coronavirus disease-2019. Initially, the virus was nCoV. Furthermore, experts from the International Committee on Virus Taxonomy (ICTV) called it the SARS-CoV-2 virus because it is very similar to the cause of the SARS outbreak. The high number of positive COVID-19 causes anxiety for nurses. Objective: This study aims to determine the relationship between the level of anxiety against COVID-19 and the risk of burnout syndrome in nurses in 2021. Methods: This study used a quantitative research design with a cross-sectional method conducted on 70 nurses at Bogor. The statistical test that will be used uses the chi-square test. Results: This study’s results showed a relationship between the level of anxiety about COVID-19 and the risk of burnout syndrome with a p-value = 0,004. Discussion: Anxiety about COVID-19 may increase the risk of burnout syndrome.